2013
DOI: 10.4103/0973-1075.121537
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial in advance stage breast cancer patients for the effectiveness on stress marker and pain through Sudarshan Kriya and Pranayam

Abstract: Objective:The objective of this study is to examine the effect of a cognitive, behavioral stress management module of Sudarshan Kriya (SK) and P on levels of serum cortisol and pain among the women suffering from advanced stage breast cancer.Materials and Methods:Participants (n = 147) were screened and randomized to receive standard care (n = 69) versus standard along with SK and Pranayam (P) intervention (n = 78) imparted in one 18 hrs workshop spread during 3 days. Participants were expected to practice it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 23 publications
1
42
0
Order By: Relevance
“…We do not know if these findings generalize to other cancer populations and particularly male patient and survivors. Currently, efforts are made to extend these findings to women with advanced breast cancer [56] as well as survivors of lung cancer [57],[58]. Although these programs are in a pilot phase, findings regarding feasibility and potential benefits are promising.…”
Section: Mind-body Practicesmentioning
confidence: 99%
“…We do not know if these findings generalize to other cancer populations and particularly male patient and survivors. Currently, efforts are made to extend these findings to women with advanced breast cancer [56] as well as survivors of lung cancer [57],[58]. Although these programs are in a pilot phase, findings regarding feasibility and potential benefits are promising.…”
Section: Mind-body Practicesmentioning
confidence: 99%
“…This breathing practice also has a role in alleviating pain involved in the pathology of certain diseases. One study demonstrated that SK and Pranayama act as an effective intervention in decreasing stress and pain among patients of advanced stage breast cancer [93]. This study was based on 147 women participants and randomized into two groups: a yoga group (n = 78) and a standard group (n = 69).…”
Section: Management Of Pain Through Pranayama and Sudarshankriya (Sky)mentioning
confidence: 99%
“…The results showed significant reduction in both the parameters as compared to the control group. Thus the study further strengthens the use of yoga in the management of neuropathic cancer pain [34] (Table 1).…”
Section: Yogamentioning
confidence: 99%